NONTHYROIDAL ILLNESS (NTIs) - Nanny Natalia Mulyani Soetedjo (Faculty of Medicine, Universitas Padjadjaran)
Nonthyroidal Illness (NTIs) didefinisikan sebagai keadaan didapatkan fungsi tiroid yang abnormal tanpa ditemukan gangguan pada aksis hipotalamus-hipofise, juga tidak ada gangguan pada kelenjar tiroidnya. NTIs ditemukan pada penderita dengan sakit berat, dan biasanya fungsi tiroid akan membaik sejalan dengan kesembuhan penyakit dasarnya. Macam-macam gangguan fungsi tiroid sangat bervariasi, mulai dari rendahnya kadar triiodotironin serum (T3) dan meningkatnya reverse T3 (rT3). Sejalan dengan beratnya penyakit dasarnya maka sering juga mengakibatkan gangguan pada thyroid-stimulating hormone (TSH), tiroksin (T4), dan free T4 (fT4). NTIs semakin berat terjadi saat kedua hormon T3 dan T4 ditemukan menurun dan secara perlahan-lahan akan meningkat sejalan dengan kesembuhan penyakitnya. Sampai saat ini masih menjadi perdebatan apakah perlu atau tidak diberikan hormon pengganti tiroid. Masih diperlukan studi prospektif dengan jumlah pasien yang besar mengenai penggunaan hormon pengganti ini. Oleh karena itu perlu untuk memahami fisiologi dan patofisiologi NTIs sehingga kita dapat memahami kapan menggunakan hormon pengganti tiroid.Kata kunci: NTIs, fungsi tiroid, hormon pengganti tiroidNONTHYROIDAL ILLNESS (NTIs)Nonthyroidal illness (NTIs) can be described as abnormal findings on thyroid function tests that occur in the setting of a nonthyroidal illness (NTI) without preexisting hypothalamic-pituitary and thyroid gland dysfunction. After recovery from an NTI, these thyroid function test result abnormalities should be completely reversible. Multiple alterations in serum thyroid function test findings have been recognized in patients with a wide variety of NTI without evidence of preexisting thyroid or hypothalamic-pituitary disease. The most prominent alterations are low serum triiodothyronine (T3) and elevated reverse T3 (rT3), leading to the general term low T3 syndrome. Thyroid-stimulating hormone (TSH), thyroxine (T4), and free T4 also are affected in variable degrees based on the severity and duration of the NTI. It cannot diagnosed NTIs only by measure one thyroid hormone. As the severity of the NTI increases, both serum T3 and T4 levels drop and gradually normalize as the patient recovers. It's still be an argument for administration of replacement T3 and T4 hormone in patients with NTIS. However, it is impossible to be certain at this time that it is beneficial to replace hormone, or whether this could be harmful. Only a prospective study will be adequate to prove this point, and probably this would need to involve hundreds of patients. Ongoing studies document the beneficial effects of replacement of other hormones in these acutely and severely ill patients.Key words: NTIs, thyroid function, hormone replacement DOI: http://dx.doi.org/10.15395/mkb.v41n3.246